Associations between 24-h heart rate variability and aerobic fitness in high-level female soccer players - Costa, J. A.; Brito, J.; Nakamura, F. Y.; Dores, H.; Rebelo, A. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Objective The aim of this study was to investigate the changes in 24-h heart rate variability and aerobic fitness, and their associations, in female soccer players during the preseason period.